Channel estimation based on the fixed DVB-S2 system to transfer images - et. al., Seksembayeva M. A., (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The growth of modern wireless communications has increased the demand for high quality data services. This article presents an analysis of the performance of a DVB-S2 system with MIMO technology. A method for using a receiver-transmitter based on DVB-S2 with MIMO technology, provides a better quality of service for data transmission and discusses ways to improve the quality of data transmission using size and type converters of transmitting and receiving data, an amplifier and a normalizer Gain. The circuit was examined for bit error rate (BER) and peak signal-to-noise ratio (PSNR) between AWGN and multipath Rayleigh fading images operating under intersymbol interference (ISI).The analysis was carried out and a graph of the influence of ISI was obtained. The proposed system has the best quality of service for data transmission for fading channels. The transmission of images in the system includes a Rayleigh channel and AWGN with different values of the signal-to-noise ratio (SNR, dB) and different values of Gain. The Gain values change the BER and PSNR values (7.834 dB, 8.385 dB, and inf) at an SNR of -58 dB with respect to Gain values of 1, 32400 and 648000, respectively. Also obtained eye diagrams, where you can see a decrease in the negative impact of intersymbol interference with an increase in the value of Gain..This system can be used to wirelessly transmit higher quality, high-resolution radiological images (such as computed tomography or magnetic resonance imaging) over a wireless network to remote healthcare workers.